Challenges and advances in nutrition for the critically ill child. Issue 4 (5th August 2022) - Albert, Ben D.; Martinez, Enid E.
Abstract : Purpose of review: Malnutrition remains prevalent in critically ill children and is associated with worse clinical outcomes. Conversely, nutrition provision has been associated with improved survival. Nutritional challenges must be addressed to guide best nutrition practices for the critically ill child. In this narrative review, we summarize findings from research published between July 2020 and January 2022 on nutrition in critically ill children. Findings from these articles build on previous work to guide next steps in both research and clinical practice in this cohort. Recent findings: A comprehensive literature review was performed. We identified the following common themes for research published between July 2020 and January 2022-metabolism, enteral nutrition, including timing, dosing, protein prescription and delivery in special populations, gastrointestinal function, and enteral nutrition adjunctive therapies. Summary: Research continues to support early initiation and advancement of enteral nutrition. Achieving nutritional adequacy is challenging, but research associated with the timing and dosing of enteral nutrition, alternative methods of enteral nutrition delivery and the use of adjuncts are expanding our understanding of best practices for this cohort. Areas for further research continue to be the use of measured energy requirements, protein dosing and inclusion of functional outcomes to assess the benefit of nutritional interventions.